Constructing future expectations in adolescence: relation to individual characteristics and ecological assets in family and friends. Issue 1 (2nd January 2018) - Iovu, Mihai-Bogdan; Hărăguș, Paul-Teodor; Roth, Maria
Abstract: Required to manage multiple developmental tasks, multiple systems and processes are involved in making adolescents thinking about and making plans for the future. The current study aims at exploring the manner in which individual (optimism, depressive symptoms, anxiety symptoms, and self-concept) and contextual factors (family and peer influences) contribute to the construction of adolescents' future expectations. 1509 youth (891 females and 618 males) with different socio-economical backgrounds were questioned using an online platform. Compared with their counterparts, girls, adolescents who were not experiencing severe material deprivation, those with high self-concept, displaying little depressive symptoms, and high level of optimism have more positive future expectations. As most of the available empirical data come from Western countries, these results complement the existing data in the area of emerging adulthood.